AN INVESTIGATIVE STUDY ON JOB SATISFACTION LEVEL OF EMPLOYEES WORKING IN SOFTWARE INDUSTRY, A VIEW POINT OF EMPLOYEES IN PAKISTAN - Sharif, Umar Fawad; Nazir, Saqib (PEOPLE: International Journal of Social Sciences, 2016)
The study aimed to examine the role of working environment, pay and promotion, job security, level of fairness, relationship with coworkers and relationship with supervisor on the job satisfaction of the employees. Survey based data was collected from 183 respondents working in the software sector. Regression analysis was used to test the impact of the independent variables of the study on the job satisfaction. The results of the research revealed that there is a positive and significant relationship between working environment, pay and promotion, job security, and level of fairness and the job satisfaction. This implies that employees who are having good working environment, have reasonable and equitable pay and promotion, have higher job security, and are treated fairly, will have higher level of job satisfaction and these employees will contribute positively towards the success and overall productivity of the organization. Similarly, good and healthy relationship with coworkers and supervisor also leads to the job satisfaction. This implies that if employees coordinate well with each other and their supervisors they can have higher level of job satisfaction and they can contribute more towards the benefit of organization then the employees who do not coordinate well. In software sector if the management want to foster the job satisfaction of the employees they should provide good working environment, good pays and they should treat the employees fairly.